Răspuns :
a)3x+5-2(x+2)=8-3(1-x)
3x-2(x+2)+5=8-3(-x+1)
3x-(2x+2•2)+5=-3(-x+1)+8
3x-(2x+4)+5=3x-3+8
x+1=3x+5
(x+1)+(-1-3x)=(3x+5)+(-1-3x)
(x+1)+(-3x+1)=(3x+5)+(-3x-1)
x+1-3x-1=3x+5-3x-1
x-3x+1-1=3x-3x+5-1
-2x=4
[tex] \frac{2x}{2} = - \frac{4}{2} \\ \\ x = - \frac{{2}^{2}}{2} \\ \\ x = - ({2}^{2-1}) [/tex]
x=-2
3x-2(x+2)+5=8-3(-x+1)
3x-(2x+2•2)+5=-3(-x+1)+8
3x-(2x+4)+5=3x-3+8
x+1=3x+5
(x+1)+(-1-3x)=(3x+5)+(-1-3x)
(x+1)+(-3x+1)=(3x+5)+(-3x-1)
x+1-3x-1=3x+5-3x-1
x-3x+1-1=3x-3x+5-1
-2x=4
[tex] \frac{2x}{2} = - \frac{4}{2} \\ \\ x = - \frac{{2}^{2}}{2} \\ \\ x = - ({2}^{2-1}) [/tex]
x=-2
a )
3 x + 5 - 2 ( x + 2 ) = 8 - 3 ( 1 - x )
3 x + 5 - 2 x - 4 = 8 - 3 + 3 x
3 x - 2 x - 3 x = 5 - 1
- 2 x = 4
x = 4 : ( - 2 )
x = - 2